DEVELOPING A DIGITAL GOVERNANCE AND BUSINESS INTELLIGENCE FRAMEWORK FOR MODERN ISLAMIC EDUCATIONAL MANAGEMENT IN HIGHER EDUCATION - Desmawati Desmawati; Evi Gusliana; Muhammad Akmansyah; Zulhanan Zulhanan; Fachrul Ghazi (JMBI (Journal of Marketing and Business Intelligence), 2026)
The rapid development of digital technology has encouraged higher education institutions to adopt integrated and data-driven governance systems to improve organizational performance and service quality. This study examines the integration of Digital Governance and Business Intelligence in developing modern Islamic educational management within a graduate program environment. A qualitative descriptive approach was employed through observations, in-depth interviews, and document analysis involving institutional leaders and academic staff. The findings indicate that the implementation of digital governance through Academic Information Systems, electronic administrative services, integrated academic and non-academic data management, and Financial Information Systems has enhanced institutional effectiveness, transparency, accountability, and service quality. The utilization of integrated data also supports evidence-based decision-making, reflecting the practical application of Business Intelligence in educational management. User satisfaction analysis involving 51 graduate students demonstrated a high level of acceptance, with an average satisfaction rate of 89.0% across academic, administrative, data management, and financial services. The study concludes that integrating Digital Governance and Business Intelligence contributes significantly to efficient, transparent, responsive, and sustainable educational management, providing a strategic model for strengthening the competitiveness of Islamic higher education institutions in the Society 5.0 era.